2002
DOI: 10.1007/bf03402008
|View full text |Cite
|
Sign up to set email alerts
|

A +2138InsCAGACC Polymorphism of the Melanocortin Receptor 3 Gene is Associated in Human with Fat Level and Partitioning in Interaction with Body Corpulence

Abstract: Background: The melanocortin system includes five receptors (MC1R to MC5R), and mouse and human MC4R has been shown to be involved in the regulation of feeding, and mouse MC3R in body composition. To verify a possible similar effect of MC3R in humans, we analyzed one insertion and one single nucleotide polymorphism by restriction fragment length polymorphisms (RFLP), and a microsatellite (D20S32e) in relation to body composition and glucose metabolism. Methods: Eight hundred twelve subjects of the Québec Famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
4
23
1
Order By: Relevance
“…Boucher et al reported the association of the ?2138InsCAGACC polymorphism, a 6 base pair insertion located 2138 base pairs Nominal P values are given for Pearson chi square analysis downstream of the MC3R start codon, and body composition related phenotypes, while again no association between V81I (rs3827103) and body composition was found. However, as the obesity-related variables BMI and body weight were not analyzed, it is difficult to compare their study with our results [16]. Although Schälin-Jantti et al also detected the rs6127698 (-373G[T) variant 5 0 of the MC3R gene, they did not genotype this SNP in their entire population, which makes comparison with our study impossible.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Boucher et al reported the association of the ?2138InsCAGACC polymorphism, a 6 base pair insertion located 2138 base pairs Nominal P values are given for Pearson chi square analysis downstream of the MC3R start codon, and body composition related phenotypes, while again no association between V81I (rs3827103) and body composition was found. However, as the obesity-related variables BMI and body weight were not analyzed, it is difficult to compare their study with our results [16]. Although Schälin-Jantti et al also detected the rs6127698 (-373G[T) variant 5 0 of the MC3R gene, they did not genotype this SNP in their entire population, which makes comparison with our study impossible.…”
Section: Discussioncontrasting
confidence: 60%
“…The MC3R gene, which maps to 20q13.2-q13.3, is therefore an excellent candidate gene for obesity research. Several research groups attempted to investigate association of variants in MC3R with obesity, but limited number of study subjects, ethnically diverse study populations and a variety of genotyping techniques led to contradictory results [10,[15][16][17][18]. In this study, we covered the entire variation in a 2 kb region around the MC3R gene.…”
Section: Introductionmentioning
confidence: 93%
“…The size of the fragments was estimated using lDNA digested with EcoR1 and HindIII as standards. The PCR conditions for typing restriction fragment polymorphisms in MC4R (MC4R-C-2745T (dbSNP database: rs7242169), MC4R-Val103Ile (dbSNP database: 2229616)) 21,22 and MC3R (MC3R-Pst1) 23 have been described elsewhere. To identify the exact location of the MC4R-C-2745T polymorphism, we screened the MC4R coding region along with 3500 bp of the 5 0 flanking region in 16 subjects with known genotype.…”
Section: Molecular Analysismentioning
confidence: 99%
“…43 The melanocortin 3 receptor and the adenosine deaminase, located approximately 10.3 and 1.3 Mb from the PLTP gene, respectively, have been significantly associated with obesity-related phenotypes. 44,45 The agouti signaling protein (ASIP) is also located within the relevant region of human chromosome 20. The ASIP is the human ortholog of the mouse agouti gene, which is a single-gene mutation model of obesity.…”
Section: Discussionmentioning
confidence: 99%